"For at her touch our lives had at last fallen into a pattern": tactility in Rebecca West's The Return of the Soldier. Issue 1 (2nd January 2021) - Kielty, Daniel
ABSTRACT: This article explores the relationship between tactility and point of view in Rebecca West's The Return of the Soldier . It uncovers how etiquette books, hand-care articles and interior design copy regulate the narrator's sensory and social perspective, arguing that her narration reconstructs and critiques the figuration of feminine tactility as an instrument of social control – one which I show was regularly employed during the Great War.